Minimum Wage Shocks, Firms and Employment: Evidence from Africa - (:unkn) unknown (My University, 2025)
Despite the widespread use of minimum wage policies to combat poverty in Africa, research on their effects remains limited. This paper addresses this gap by examining the economic impact of minimum wage shocks on firms across the African continent using firm-level data from the World Bank Enterprise Surveys. We document that all but four African countries have a minimum wage system. Between 2002 and 2019, we identify 13 shocks-defined as a 30% real increase-in 11 countries. Employing a difference-in-differences approach, we estimate the causal effects of these shocks on labor costs, employment, sales, and productivity. To address potential endogeneity, we instrument minimum wage changes using social protest intensity. We find that minimum wage shocks significantly increase labor costs per worker, suggesting at least a partial enforcement of regulations. However, we detect no robust impact on employment. Instead, firms partly offset higher labor costs through increased sales or productivity. We identify three complementary mechanisms: (1) a cleansing effect, where less productive firms exit; (2) capital investment as an adjustment channel; and (3) a local demand boost, with stronger sales effects in large markets.
Keywords: African Research